A Sensitivity Approach to Model Local Voltage Controllers in Distribution Networks - Dzafic,I; Jabr,RA; Halilovic,E; Pal,BC (IEEE Transactions on Power Systems, 2014)
Local controllers are essential in distribution networks;they are employed in classical devices such as loadtap-changing (LTC) transformers and switchable shunt capacitors,and more recently in distributed generation (DG). Theeffective use of distribution management system (DMS) applicationsrequires an accurate model of the interaction betweenthe local controllers through the distribution system. This paperpresents a new sensitivity matrix approach for modeling suchinteractions, and demonstrates its application in the implicitGaussmethod for power flow computation. The sensitivity methodmodels both PV buses (for the connection of DG) and tap positionadjustments through current source injections, and consequentlyavoids re-factorization of the network bus admittance matrix.Numerical results on distribution networks with up to 3145 busesshow that the sensitivity-based power flow method for simulatingthe operation of local controllers is superior to a sequentialcontrol action adjustment approach previously proposed in theliterature, and that its computing time is commensurate with theperformance requirements in real-time DMS applications.